Leituras do amor em arrochanejo: discurso, sujeito e verdade - Mota, Tamize da Silva (2022)
This dissertation is based on Foucauldian discursive studies and aimed to analyze the truth/lie discourses produced in the audiovisualities of arrochanejo. The investigation was carried out by reading about love based on clips by Gustavo Mioto, Toninho Magalhães and Luydi and Luiz, who were chosen precisely because they address the issue of fake news in love relationships; thus allowing to identify how the production of truths takes place as well as the characterization of the space of constitution of this love-truth relationship that is crossed by knowledge/power, demonstrated in this way how the subject who loves is constituted according to his historical-social context. The methodology used was the analysis of audiovisualities based on Michel Foucault's theory, and, for that, I made an archeogenealogy of love utterances to understand the discourses of love today, noting there are discursive regularities in the studied arrochanejo clips of which men are always victims. of a woman's false love and the formation.